A thermal non-equilibrium model for 3D double diffusive convection of power-law fluids with chemical reaction in the porous medium. (December 2017) - Zhuang, Y.J.; Yu, H.Z.; Zhu, Q.Y.
Highlights: Study the thermosolutal convection in a porous cubic cavity filled in power-law fluids under the LTNE state. Simulate the 3D convection with the compact high order finite volume method. Reveal the shear-thinning fluid is more effective on the change of flow structure, heat and mass transfer. Find the effect of chemical reaction parameter on heat and mass transfer. Abstract: The article reports a numerical study of the double-diffusive natural convection of power-law fluids in a porous cubic cavity with chemical reaction under the local thermal non-equilibrium (LTNE) state and submitted to horizontal temperature and concentration gradients. The complete governing equations, in which the generalized non-Darcy model is employed as momentum equation and a two-temperature model that represents temperature fields of the fluid and solid phases separately is used for energy equation, are solved by the compact high order finite volume method. Special attentions are given to detecting the effects of the porosity modified conductivity ratio ( γ ), the inter-phase heat transfer coefficient ( H ), the chemical reaction parameter ( λ ), the Dufour parameter ( Du ), the Soret parameter ( Sr ) and the Lewis number ( Le ) on the fluid flow as well as on rates of heat and mass transfer. Our simulations show that the heat transfer rate of solid increases, while the heat transfer rate of fluid and mass transfer rate keep constants, as the LTNE parameters (i.e., γ and H ) increase. For any relatively large value of γ and H, the almost thermal equilibrium state is achieved due to the similar thermal distribution of fluid and solid phases. On the contrary, the chemical reaction parameter has significant influence on mass transfer than on heat transfer under the LTNE conditions. In addition, the heat and mass transfer enhance with the increment of the Soret and Dufour parameters. Augmentation of Lewis number enhances mass transfer but reduces heat transfer. Apart from that, our numerical tests show the flow field is influenced appreciably by the presence of the power-law index (n), Darcy number ( Da ) and porous thermal Rayleigh number ( Ra ).